Hermaphroditism in Marijuana (Cannabis sativa L.) Inflorescences – Impact on Floral Morphology, Seed Formation, Progeny Sex Ratios, and Genetic Variation - Punja, Zamir K.; Holmes, Janesse E. (Frontiers in Plant Science, 2020)
Cannabis sativa L. (hemp, marijuana) produces male and female inflorescences on different plants (dioecious) and therefore the plants are obligatory out-crossers. In commercial production, marijuana plants are all genetically female; male plants are destroyed as seed formation reduces flower quality. Spontaneously occurring hermaphroditic inflorescences, in which pistillate flowers are accompanied by formation of anthers, leads to undesired seed formation; the mechanism for this is poorly understood. We studied hermaphroditism in several marijuana strains with three objectives: (i) to compare the morphological features of this unique phenotype with normal male flowers; (ii) to assess pollen and seed viability from hermaphroditic flowers; and (iii) to assess the effect of hermaphroditism on progeny male:female (sex) ratios and on genetic variation using molecular methods. The morphological features of anthers, pollen production and germination in hermaphroditic flowers and in staminate inflorescences on male plants were compared using light and scanning electron microscopy. Seeds produced on hermaphroditic plants and seeds derived from cross-fertilization were germinated and seedlings were compared for gender ratios using a PCR-based assay as well as for the extent of genetic variation using six ISSR primers. Nei’s index of gene diversity and Shannon’s Information index were compared for these two populations. The morphology of anthers and pollen formation in hermaphroditic inflorescences was similar to that in staminate flowers. Seedlings from hermaphroditic seeds, and anther tissues, showed a female genetic composition while seedlings derived from cross-fertilized seeds showed a 1:1 male:female sex expression ratio. Uniquely, hermaphroditic inflorescences produced seeds which gave rise only to genetically female plants. In PCR assays, a 540 bp size fragment was present in male and female plants, while a 390 bp band was uniquely associated with male plants. Sequence analysis of these fragments revealed the presence of Copia-like retrotransposons within the C. sativa genome which may be associated with the expression of male or female phenotype. In ISSR analysis, the percentage of polymorphic loci ranged from 44 to 72% in hermaphroditic and cross-fertilized populations. Nei’s index of gene diversity and Shannon’s Information index were not statistically different for both populations. The extent of genetic variation after one generation of selfing in the progeny from hermaphroditic seed is similar to that in progeny from cross-fertilized seeds.